Enhanced ultraviolet-B radiation reduces methane emission in one of the oldest and largest rice terraces in China but triggers new challenges - Yan, Kai; Wang, Can; Li, Xiang; Li, Mingrui; Zhan, Fangdong; Li, Zuran; Li, Yuan; He, Yongmei (Frontiers in Earth Science, 2023)
Ultraviolet-B (UV-B) radiation enhancement and climate warming are two critical environmental issues worldwide. Understanding the effects of enhanced UV-B radiation on methane (CH4) emission and rice growth in paddy fields are fundamental for human sustainability. In situ field experiments with ambient and supplemental UV-B radiation stresses were conducted in paddy fields subjected to prolonged flooding at Yuanyang Terraces, Southwest China. Annual dynamics and driving factors of CH4 emission were investigated; the effects of enhanced UV-B radiation on soil carbon conversion, enzyme activities and rice growth were studied. Yuanyang Terrace’s CH4 emission levels were 1.6 and 3.3 times higher than China’s and global mean values, respectively. Weather conditions (27.02%) and the stage of rice cultivation (25.65%) were the predominant factors in driving CH4 emission. During the winter fallow period, enhanced UV-B principally affected rice straw and its decomposition, subsequently changing both soil enzyme activities and labile organic carbon levels to reduce CH4 emission. On the other hand, during the rice-growing period, enhanced UV-B affected rice growth, subsequently changing rhizospheric microorganism and soil enzyme activities to reduce CH4 emission. Meanwhile, enhanced UV-B could affect the growing of rice to further change the balance between CH4 and CO2 in the rhizosphere, and the corresponding trade-off could reduce the shifts in global warming potential of rice terraces. In total, enhanced UV-B reduced CH4 emission in the rice terraces by 15.70%, but would increase CO2 and N2O emissions, and negatively affect paddy yields, thus hindering regional food security and sustainable development. Therefore, integrating a consideration of the mitigation of greenhouse gas emissions with a concern for food security is a prospect for future research.